2021
DOI: 10.1371/journal.pone.0261137
|View full text |Cite
|
Sign up to set email alerts
|

Genetic risk factors associated with gestational diabetes in a multi-ethnic population

Abstract: Aims Genome-wide association studies have shown an increased risk of type-2-diabetes (T2DM) in patients who carry single nucleotide polymorphisms in several genes. We investigated whether the same gene loci confer a risk for gestational diabetes mellitus (GDM) in women from Hawaii, and in particular, Pacific Islander and Filipino populations. Methods Blood was collected from 291 women with GDM and 734 matched non-diabetic controls (Pacific Islanders: 71 GDM, 197 non-diabetic controls; Filipinos: 162 GDM, 395… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 60 publications
1
15
0
Order By: Relevance
“…GRB10 (rs933360) node has strong interaction with the IRS1 node, an insulin receptor substrate 1 that may mediate the control of various cellular processes by insulin. It is associated with diabetes in some studies ( 32 34 ), and with both diabetes and GDM in other ( 35 , 36 ). We have found an association with GDM in the Hispanic ethnic stratum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GRB10 (rs933360) node has strong interaction with the IRS1 node, an insulin receptor substrate 1 that may mediate the control of various cellular processes by insulin. It is associated with diabetes in some studies ( 32 34 ), and with both diabetes and GDM in other ( 35 , 36 ). We have found an association with GDM in the Hispanic ethnic stratum.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the nodes in Figure 2 have the name of a locus/gene that are well referenced in the literature because several SNPs with a significant association with diabetes and GDM are located nearby. Specifically, the nodes located in the central core of the graph, MNTR1B (rs1387153, rs10830962, rs10830963), IGF2BP2 (rs4402960, rs7651090), KCNJ11 (rs5215), GCKR (rs780094), CDKAL1 (rs9368222), IRS1 (rs2943634), ADRA2A (rs10885122), CRY2(rs11605924), DKGB (rs2191349), G6PC2 (rs563694), GLIS3 (rs7041847, rs7034200, rs10814916), GIPR (rs2302593), WFS1 (rs4458523), ZBED3 (rs7708285), PROX1 (rs340874), FOXA2 (rs6048205), PDX1 (rs2293941), PCSK1 (rs6235), have been referred in various GWAS as associated to diabetes ( 6 , 19 25 ), GDM ( 26 34 ) or both ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, previous research has demonstrated that the T allele of rs13266634 protects against the risk of GDM in the Swedish population ( 8 ), which was consistent with our findings. Moreover, in populations of Filipinos, Swedes, Koreans, and Chinese individuals, there was evidence of an association between the C allele of SLC30A8 rs13266634 and a higher risk of GDM ( 8 , 13 , 14 , 18 ). However, other studies have not found any association between rs13266634 and the risk of GDM in populations of Danes and Europeans ( 15 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another study suggested that SLC30A8 rs13266634/T is a protective variant against the development of GDM among European women (46). SLC30A8 rs13266634/T also showed significant associations with GDM among Filipinos (52). Furthermore, SLC30A8 rs3802177 was also significantly associated with the risk of GDM (25).…”
Section: Zinc Transporter-8 Genementioning
confidence: 99%